A PRE-EXPERIMENTAL STUDY TO ASSESS THE EFFECTIVENESS OF A STRUCTURED TEACHING PROGRAM FOR THE IMPROVEMENT OF KNOWLEDGE REGARDING HUMAN MILK BANKING AMONG NURSING STUDENTS AT JANAKPURDHAM, NEPAL - Yadav, Punita; Yadav, Poonam; Kumar Bhinawar, Sunil; Mahato, Srijana; Pandey, Smita (Journal of Chitwan Medical College, 2024)
Background: Human milk bank or breast milk bank is a service which collects, screens, processes and dispenses by prescription human milk donated by nursing mothers who are not biologically related to the recipient infant. Human milk is equally beneficial for all newborn babies. Nurses are one to be in direct touch with nursing mother in hospital and community. Therefore, this study aimed to assess the knowledge regarding human milk banking among nurses. Methods: A pre-experimental one group pre-test posttest study was adopted for the study. Convenient sampling techniques were used for sampling technique. Obtained data were analyzed using SPSS version 24 for windows to obtain the descriptive statistics such as frequency, percentage, mean and standard deviation. Results: The findings revealed that the overall mean pre-test Knowledge score was 11.50 their Standard deviation was 3.83 and the overall post-test knowledge score was 22.62 its standard deviation was 4.19 respectively. The mean post-test knowledge score of nursing students who were exposed to structured teaching programme are significantly higher, than the mean pretest knowledge scores. Conclusions: The study concluded that the structured teaching Program was an effective teaching strategy, to enhance knowledge of nursing students regarding human milk banking. In addition, nurses play a vital role in raising public awareness regarding the establishment of breast milk banks. It will aid in enhancing neonatal health and helps in lowering infant mortality rate.